Study on the policy diffusivity of China’s marine strategic science and technology power building based on LDA modelling - Fu, Yufang; Xu, Hui; Wang, Yi; Chen, Fang; Gu, Bojun (Frontiers in Marine Science, 2025)
The world's maritime countries are competing for the strength of marine science and technology. Throughout the world, the systematic construction of marine strategic scientific and technological strength has become a decisive factor in marine scientific and technological competition, and it is an inevitable choice for China to cope with marine scientific and technological competition. As far as science and technology policy is concerned, the efficiency of policy supply directly affects the effect of science and technology implementation. Therefore, it is urgent to clarify the mechanism of policy diffusion that influences the development of marine strategic scientific and technological forces. This paper employs a case study approach to examine the diffusion characteristics of China's marine science and technology policies. The analysis is based on the marine science and technology policies issued by the Chinese government at the central, provincial and municipal levels since 2002. The study employs an LDA model and text-mining techniques in the R language to construct a comprehensive understanding of the diffusion process. The study reveals that China's marine science and technology development policies exhibit a top-down diffusion trend. Furthermore, the implementation intensity and responsiveness of lower-level governments to higher-level policies are increasing. The diffusion of policy themes displays clear temporal characteristics, with policies undergoing continual refinement in the context of top-down content diffusion. However, there is less interaction between bottom-up policies. In this regard, we should improve the overall effectiveness of the marine strategic scientific and technological strength policy system, optimize the policy diffusion mechanism of marine strategic scientific and technological strength, and strengthen the construction of a public participation consultation system to strengthen the overall play of China's marine strategic scientific and technological strength.